Analisis Kemampuan Kewirausahaan Pengusaha Perempuan pada Komunitas UMKM Masyarakat Kota di Indonesia - Titis Tatasari; Ketut Witara (Journal of Management and Social Sciences, 2024)
Women are a valuable resource who can contribute significantly to increased economic development. But the contributions made by women are sometimes less than those of males. Nonetheless, a lot of prosperous female business owners choose to enter the realm of economic entrepreneurship, particularly in the home. Women possess a number of qualities, such as strong drive and the ability to work autonomously to boost productivity via participation in many forms of education and training. Women contribute to the economy by being more inventive and creative in problem-solving and seizing possibilities that present themselves to individuals on a daily basis. Analyzing and identifying a woman entrepreneur's entrepreneurial skills in an urban MSME community is the goal of this study. This research retrieves and manages data through identifying problem topics by conducting searches based on research keywords in various sources such as Google Scholar, Sciencedirect, Sage Journal, and other trusted sources. The data obtained is then analyzed critically by reviewing the ideas, knowledge and findings contained in the literature that has been collected. The research results show that education, experience and attitudes towards risk taking are very important in the entrepreneurial activities of female entrepreneurs